A house divided: asset-based welfare and housing asset-based welfare. Issue 2 (3rd April 2019) - Prabhakar, Rajiv
Abstract: Asset-based welfare (ABW) is a policy approach that claims the individual ownership of assets is important for individual welfare. It is concerned mainly with small amounts of financial wealth and has sparked growing scholarly criticism that argues that it ignores the dominant role of housing as a type of asset. This housing asset-based welfare (HABW) critique also charts the ways that ABW leads to pathologies in housing markets. A major problem for ABW though is that HABW has emptied ABW of its original content. This paper claims that this results in a 'house divided', that is two separate literatures that both purport to study assets but talk past one another. This paper suggests that research would be enhanced by a greater dialogue between these different literatures. It further argues that a theme of egalitarian property-owning democracy is a way of uniting these different literatures. Creating an egalitarian property-owning democracy suggests that there should be shared research on taxing housing wealth and developing new models of home ownership.